Performance of four rubber tree clones at the Ribeira river valley, state of São Paulo, Brazil - Gonçalves, Paulo de Souza; Cardoso, Mario; Sáes, Luiz Alberto (Pesquisa Agropecuaria Brasileira, 1991)
The present article shows the performance of eight year-old rubber tree clones (Hevea spp.), Fx 3844, Fx 3864, Fx 567 and IAN 717 grown in producer areas. Plant vigour, wind damage, and resistance to the South American leaf blight (SALB) were used as descriptors for clone evaluation. Yield potential and susceptibility to brown blast, related to each clone were evaluated from data from different regions of Brazil with the same conditions. The clones Fx 3844, Fx 3864 and Fx 567 showed the percentages of 89.20%, 65.38% and 47.69% of the trees in conditions to be tappable at eight years of age. Due to the susceptibility to wind damage, it was suggested to avoid steep terrain to plant the clone Fx 3864 because of the accentuated force of the wind on these spots. The IAN 717 clone is not recommended to be planted in the Ribeira Valley due to its low growth, moderate incidence of SALB and brown blast.
Keywords: Hevea; wind resistance; Microcyclus ulei; brown blast coefficient of variation; variation coefficient